INTEGRATION OF SOCIAL SCIENCES IN STUDENT CHARACTER EDUCATION BASED ON THE PANCASILA PROFILE - Marsini (RADJA PUBLIKA, 2021)
This study explores the contribution of social science learning in the formation of student character based on the Pancasila Student Profile in high schools. The research method used is qualitative with data collection techniques through interviews, observations, and documentation. The results of the study show that social sciences, such as history, geography, sociology, and economics, play an important role in instilling Pancasila values, including mutual cooperation, global diversity, independence, and democracy. Teachers use active learning strategies, such as project-based learning and group discussions, to facilitate students' understanding of these values. These findings support a constructivist learning theory that emphasizes student involvement in the learning process. Nevertheless, this study identifies obstacles, such as limited time and resources as well as variations in teacher competence. The research also emphasizes the importance of collaboration between schools, families, and communities in supporting character education. The implications of this study are the need to develop a more contextual curriculum, improve teacher competence, and strengthen cooperation between schools and communities. Social science learning, if applied correctly, can be an effective means to form student character in accordance with Pancasila values.